Implementation of the Free Nutritious Meals (MBG) Program: A health policy perspective from Jakarta - Babo, Djimmy Heru Purnomo; Sidi, Khayla Raslina; Imtiyaz, Hulwah (Jurnal Cakrawala Promkes, 2026)
The Free Nutritious Meals (MBG) Program is a flagship initiative of the Indonesian Government aimed at addressing malnutrition and strengthening human capital development. The program seeks to improve access to nutritious food, reduce stunting, and support the development of a healthy and competitive generation toward Indonesia’s Golden Age 2045. This qualitative descriptive study was conducted at SMP X Jakarta. Data was collected through in-depth interviews with field implementers directly involved in program execution. The analysis focused on examining implementation processes through a health policy perspective. The findings indicate that the program aligns with core health policy principles, particularly in promoting health through school-based interventions. Field implementers reported that the program contributes to meeting students’ nutritional needs and is associated with improved concentration and school attendance. The program has received strong support from students and parents, who perceived it as relevant to household economic conditions and children’s health needs. However, several challenges were identified, including diverse student consumption behaviors, a large target population, limited facilities, and suboptimal food preparation processes. Additionally, the absence of detailed operational guidelines, limited technical training, and unclear division of authority required schools to independently adjust the implementation mechanism. While the MBG program demonstrates substantial benefits in supporting student nutrition and educational engagement, strengthening governance structures, technical guidance, and operational coordination is essential to optimize program sustainability and scalability.